PENGARUH DOMINASI METODE CERAMAH TERHADAP TINGKAT PEMAHAMAN BELAJAR MAHASISWA PADA MATA KULIAH PEMBELAJARAN TERPADU DI KELAS 4D PGSD UNIVERSITAS NUSA CENDANA KUPANG - Novelsi Sanggu, Rinian; Filipus Rasul Rosari Nasir; Ignasius Hary Lassa; Maria Yuliana Picauly; Maria Yunita Monga; Gaudensius Jati Lamauran Koten; Hiwa Wonda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the dominance of the lecture method on students’ learning comprehension in the Integrated Learning course among Class 4D students of the Elementary School Teacher Education Program (PGSD) at Nusa Cendana University, Kupang. The study was motivated by the continued dominance of lecture-based instruction in higher education, which may influence students’ understanding of course materials. A quantitative approach with a correlational design was employed. The population consisted of all 33 students enrolled in Class 4D PGSD, and the sampling technique used was total sampling. Data were collected through questionnaires measuring the dominance of the lecture method and students’ learning comprehension. The data were analyzed using descriptive statistics, reliability testing, simple linear regression analysis, coefficient of determination, and t-test with the assistance of SPSS software. The results revealed that the dominance of the lecture method had a positive and significant effect on students’ learning comprehension. The simple linear regression analysis produced the equation Y = 17.660 + 0.399X, indicating that an increase in the dominance of the lecture method was associated with an increase in students’ comprehension levels. The t-test showed a significance value of 0.041, which was lower than 0.05, confirming that the effect was statistically significant. Furthermore, the coefficient of determination (R²) was 0.177, indicating that the dominance of the lecture method contributed 17.7% to students’ learning comprehension, while the remaining 82.3% was influenced by other factors. Therefore, the study concludes that the dominance of the lecture method significantly affects students’ learning comprehension, although its contribution remains relatively low.